(untitled) (PAAN Journal, 2026)
Nepal’s adoption of federalism following the 2015 Constitution introduced a transformative shift in its governance framework, particularly affecting disaster response structures in a country highly vulnerable to seismic events. This research investigates how federal restructuring has shaped the effectiveness, coordination, and resilience of earthquake management efforts. Centered on the post-2015 landscape, the study uses a qualitative methodology relying exclusively on secondary data, including government policy frameworks, development agency reports, academic literature, and media analysis. Special attention is given to evaluating the delineation of roles across federal, provincial, and local governments, as well as to assessing institutional capacity-building and intergovernmental collaboration in the aftermath of the 2015 Gorkha earthquake. The findings highlight notable strengths such as increased local autonomy and improved community engagement, while also revealing persistent bottlenecks in resource allocation, coordination protocols, and policy implementation. Despite formal decentralization, lingering centralization in funding and decision-making hampers timely and inclusive disaster response. This study concludes with targeted policy recommendations to enhance federal resilience, promote effective cross-tier coordination, and strengthen local governments’ operational capacities in earthquake-prone areas. By bridging gaps in disaster governance, Nepal’s federal model can serve as a blueprint for resilient, community-driven emergency systems in similarly vulnerable contexts.